Human trafficking: factors that influence willingness to combat the issue. Issue 9 (19th March 2016) - Honeyman, Katherine L.; Stukas, Arthur A.; Marques, Mathew D.
Abstract: Human trafficking involves severe violations of human rights and social action is required to combat it. Past research has identified emotional reactions to victims of trafficking, as well as the perceived cost and efficacy of actions, as significant predictors of willingness to get involved. We surveyed 216 Australians (70% female) to assess their perceptions of sex and labor trafficking and actions to reduce them. Results demonstrated that women reported greater personal distress (but not empathy) for victims than men, which was associated with greater willingness to take action. Women also perceived available actions to be more efficacious than men, which predicted willingness, while perceived cost of actions did not. Implications for promoting social action to reduce human trafficking are discussed.